Recent Advances in C(sp3)–C(sp3) Cross-Coupling via Metallaphotoredox Strategies - Zheng, Songlin; Hu, Yuanyuan; Yuan, Weiming (Synthesis, 2021)
Transition-metal-catalyzed carbon–carbon cross-coupling reactions represent a significant achievement in modern synthetic chemistry and they have become indispensable tools for the construction of organic molecules. Despite the important progress in this area, methods for coupling two C(sp3)-hybridized alkyl fragments remain elusive. To date, existing methods have largely relied on using organometallic reagents as the nucleophilic coupling partners, thereby inevitably limiting the compatibility of functional groups. Although cross-electrophile coupling may alleviate the pain somewhat, it is necessary to add a stoichiometric amount of a reductant to complete the catalytic cycle. Recently, the emergence of photoredox-mediated single-electron transmetalation has evoked an ideal paradigm for selectively manipulating C(sp3)–C(sp3) cross-coupling with the unprecedented application of native C(sp3) functionalities instead of organometallic reagents, thus opening a new window for C(sp3)–C(sp3) bond creation. This short review highlights the recent advances in this exciting subfield.1 Introduction2 Nickel/Photoredox-Catalyzed C(sp3)–C(sp3) Cross-Coupling3 Palladium/Photoredox-Catalyzed C(sp3)–C(sp3) Cross-Coupling4 Copper/Photoredox-Catalyzed C(sp3)–C(sp3) Cross-Coupling5 Direct C(sp3)–H Alkylation via Metallaphotoredox-Mediated Hydrogen Atom Transfer6 Conclusion and Perspectives
Keywords: metallaphotoredox catalysis; C(sp3)–C(sp3) cross-coupling; nickel; palladium; copper; hydrogen-atom transfer (HAT)